MENANAMKAN NILAI-NILAI TOLERANSI SEJAK DINI DI MI MA’HAD AL-ZAYTUN: UPAYA MEWUJUDKAN PERDAMAIAN DUNIA DI MASA DEPAN - Abdul Jabar, Muhamad; Saputra, Wiwin; Widodo, Sri; Nabila, Muthia (Cahaya Ilmu Bangsa Institute, 2024)
Tolerance is an attitude that reflects mutual respect and acknowledgment of differences and diversity within society, with the main goal of creating a peaceful and harmonious life. More than just accepting differences, tolerance also serves as a foundation for building solidarity, where individuals are able to embrace and appreciate each other’s uniqueness and transform uniformity into a rich and dynamic diversity. The primary objective of this research is to understand how tolerance values are introduced and developed among students from an early age and to measure their impact on character development. This study also aims to provide recommendations for developing more effective educational programs to instill tolerance values. The research uses a qualitative approach. The data sources include books such as